PENGARUH LIKUIDITAS, PROFITABILITAS DAN LEVERAGE TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN SUB SEKTOR FOOD AND BEVERAGE YANG TERDAFTAR DI BEI TAHUN 2017 - 2019 - Suseno Hendratmoko (Pusat Riset dan Inovasi Nasional, 2022)
This research aims to determine the degree to which liquidity, profitability, and leverage affect dividend policy in Food and Beverage Sub Companies listed on the IDX from 2017 to 2019. Purposive sampling is conducted in this kind of quantitative study, with up to 11 samples drawn from a total of 32 organizations. In this study, the following analytical tools were applied: the Validity Test, Reliability Test, Classic Assumption Test, Multiple Linear Regression Analysis, t Test, F Test, and Coefficient of Determination Test. To the study's findings based on the limited test, liquidity significantly affects dividend policy. Leverage has a low positive impact on dividend policy as well as a low positive impact on profitability.